Good Samaritans vs. predatory peddlers: problematizing the war on overdose in the United States - McLean, Katherine (Journal of crime and justice, 2018)
In the wake of dramatic increases, and demographic shifts, in the misuse of heroin and prescription opioids, drug addiction and accidental overdose have been increasingly framed as public health, not criminal justice, matters in the United States. In turn, many locales hardest hit by fatal overdose have supported so-called ‘harm reduction’ policies aimed at stemming opiate-related mortality, while openly disclaiming the propriety of strategies that punish users. Yet, as U.S. overdose deaths achieved another record high in 2015, individual users continue to fear the criminal ramifications of witnessing and even suffering an overdose. Using surveys and interviews among a sample of overdose-experienced individuals outside Pittsburgh, PA, this study reveals a marked reluctance among those at the scene of an overdose to involve emergency services, for fear of not only maltreatment, but also prosecution on homicide charges - a fear revealed to be well-justified in light of the increasing implementation and enforcement of ‘fatal drug delivery’ laws. Reflecting on Jonathan Simon’s depiction of the U.S. as a society ‘governed through crime,’ this paper considers how an emergent ‘war on overdose’ may serve to buttress and quietly sustain an unpopular ‘war on drugs’ through alternative tactics that identify new victims and offenders.